Pengaruh Kualitas Air Terhadap Produksi Ikan Lele Dumbo (Clarias gariepinus) - Afdan, Rifqi Khoir; Khairuddin, Faritz; Mawla Lubis, Muhammad Fazil; Tsaabitahusnaa; Hasibuan, Febry Rahmadhani (Indonesian Journal Publisher, 2023)
Catfish is the most popular freshwater fish by the community, because of its ease of cultivation and affordable price, so many beginner catfish farmers choose this fish as a mainstay commodity. This research was conducted on a catfish farm in sampali village, kec. Percut sei tuan. on August 15, 2023, the methods used in this research are surveys and interviews. The tools used to conduct the survey were a smartphone used for audio and visual documentation of the results of surveys and interviews taken from the farm where the survey was conducted and a ruler to measure the survey results periodically. Data collection was conducted twice during 2 months. The catfish cultivated in the Sampali CatfishFarm pond is Dumbo catfish. Based on the results of interviews that have been conducted by the author to the owner of the catfish farm, Mr. Agus Suprianto, the author concludes that Mr. Agus Suprianto has experienced obstacles in cultivating Dumbo catfish due to limited tools to measure the pH level of the pond water and can control the water quality of the pond which is used as a cultivation of Dumbo catfish. Pond owners can only estimate changes in water pH from the behavior of fish that often float on the surface of the water. The purpose of this study was to determine the effect of differences in water cleanliness on the development of catfish.